MENGENAL á¹¢IGAT-á¹¢IGAT DALAM MEREPRESENTASIKAN HADIS: - Mulizar (Al-Bukhari : Jurnal Ilmu Hadis, 2019)
In terms of sanad and matan, or based on the strengths and weaknesses, the Hadith is divided into two groups, namely: the hadith maqb?l and the hadith mard?d. One way to find out a hadith whether the hadith is accepted or mard?d can be seen from the ??g?t. ??g?t Hadith is divided into two groups, namely ??g?t Jazm and ??g?t Tamr??. An assessment of a Hadith is incomplete if we have not discussed  ??g?t al-Jazm and  ??g?t at-Tamr??. This needs to be done to understand how the Hadith is classified. In determining the laws of  ??g?t al-Jazm and  ??g?t at-Tamr?? the Ulama of Hadith have explained that if the Hadith is a hadith ?a??f, then it is not allowed to exchange it with active sentences ( ??g?t al-jazm) such as: said the Messenger of Allah. mention the narration of the hadith ?a??f from the tabiin circles by using  ??g?t al-jazm, but by using  ??g?t at-tamr?? as the words q?la, ruwiya, ?ukiya and so forth. This article provides knowledge to the reader, namely how to recognize the traditions through the  ??g?t expressed in a hadith and give insight to the traditions that are ambiguous and mard?d through  ??g?t in a hadith, and express how the opinion of the hadith scholars about the  ??g?t.